Swearing-in Ceremony for New Attorneys Held at Wine Press Room at Selland Arena - Watkins, Howard::::::::: (1989)
State Bar District 5 Governor Robert Oliver with raised left hand noting that your word is your bond. If you lose it, you may never get it back